Southern Products - (:unkn) unknown (My University, 2009)
An infant sitting in a basket filled with cotton. Affixed to the postcard is a US 1 cent stamp, postmarked February 19th, 1913
Colour; Coloured; Style: Portrait; Other: Unbordered, Undivided
Keywords: Postcards; Children; Wicker baskets; Cotton; 1913